ANALISA JALUR DALAM CORPORATE ENTREPRENEURSHIP TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PERUSAHAAN KELUARGA DI JAWA TIMUR) - Ratih Indriyani (Kompetensi (Competence : Journal of Management Studies), 2014)
Corporate entrepreneurship is en important factor in family business that creates outcome non financial  in organization, such as human resource like organizational commitment and organizational citizenship behavior (OCB) . The aim of this study is to examine the impact of Corporate Entrepreneurship on OCB, through organizational commitment as an intervening variable. Data is collected with total respondents of 134 samples by using purposive sampling method.  By using a path analysis, the result shows that corporate entrepreneurship have direct impact  to OCB and indirect impact exists from corporate entrepreneurship to OCB through organizational commitment as an intervening variable . Direct impact of corporate entrepreneurship  to OCBis 0,199. Indirect impact  of corporate entrepreneurship  to organizational commitment  that is P2 is 0,501 meanwhile from organizational commit OCB , that is P3 is 0,772, therefore indirect influence, that is P2 times P3 is (0,501)*(0,772)=0,387. Total impact of corporate entrepreneurship  to OCBis more than 0,5, 0,199+ 0,387 = 0.586